1976
DOI: 10.1007/bf00445778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of paracetamol-induced damage in liver biopsies

Abstract: In 100 patients who had taken an acute overdose of paracetamol the liver was biopsied percutaneously on the 4th day or as soon thereafter as recovery of the clotting mechanism allowed. A system for grading the histological changes in the liver is described. The hallmark of severe (grade III) damage is centrizonal necrosis, for which there is probably a dosage threshold. Consequent changes include phagocytosis of cell debris, reticulin collapse, and an inflammatory infiltration; acidophil degeneration of hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The pathological investigation revealed marked microvesicular and macrovesicular fatty change as well as necrosis and hemorrhage preferentially localized in the pericentral area [19] and also showed infiltration of lymphocytes and inflammatory changes in the periportal area. From these findings, liver damage induced by toluene is considered to be the result of a direct cytotoxic effect [21]. One experimental animal study showed that exposure to toluene at concentrations of 533-800 ppm for 7 days increased liver weights, and electron microscopical examination revealed ultrastructural changes that were compatible with changes in cytochrome P-450 concentrations [22].…”
Section: Discussionmentioning
confidence: 98%
“…The pathological investigation revealed marked microvesicular and macrovesicular fatty change as well as necrosis and hemorrhage preferentially localized in the pericentral area [19] and also showed infiltration of lymphocytes and inflammatory changes in the periportal area. From these findings, liver damage induced by toluene is considered to be the result of a direct cytotoxic effect [21]. One experimental animal study showed that exposure to toluene at concentrations of 533-800 ppm for 7 days increased liver weights, and electron microscopical examination revealed ultrastructural changes that were compatible with changes in cytochrome P-450 concentrations [22].…”
Section: Discussionmentioning
confidence: 98%
“…Fourteen patients (1-14) had uninformative profiles. Three patients (15)(16)(17) showed marked elevation of free carnitine. Ten patients (18 -27) had elevated concentrations of medium-or long-chain species.…”
Section: Discussionmentioning
confidence: 99%
“…14 Microvesicular steatosis is a common although not universal finding in FAO defects, but it is distinctly uncommon in acetaminophen toxicity. 14,17,18 Interestingly, in one of the few other reported cases of steatosis in acetaminophen toxicity, the outcome was unexpectedly fatal. 18 A third alternative is that these patterns in bile are markers of a specific type of liver injury possibly related to an unknown toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte regeneration is seen as early as 4 days after acetaminophen overdose. 10 These cases differ from other cases of MHN because the inflammatory cell component is usually mild or nonexistent initially. 11 Inflammation increases later, with a longer overdose to tissue sampling interval as regeneration begins.…”
Section: Histopathology Of Massive Hepatic Necrosismentioning
confidence: 95%